Self-Directed Learning Outcomes and Facilitators in Virtual Training of Graduate Students of Medical Education - Masoumeh Safikani; Noushin Kohan; Yunes Jahani; Esmat Nouhi (Strides in development of medical education (Online), 2021)
Background: Although virtual training has been considered an educational emergency during the coronavirus crisis, it is still discussed in universities as a capacity. Student learning is the concern of all professors. Self-direction is an efficiency indicator in electronic learning (e-learning) widely used in effective educational systems.Objectives: The present study aimed to determine self-directed learning outcomes and facilitators in virtual course students of medical education.Methods: The statistical population of this descriptive-analytical cross-sectional study included the graduate of virtual medical education in the universities of medical sciences in Tehran, Iran, in the academic year 2019. The research instrument was the Persian version of the Self-Directed Learning Readiness Scale. Data analysis was performed using SPSS software (version 16), the indicators of descriptive statistics (e.g., mean, frequency, percentage, and standard deviation), linear regression, and Pearson correlation coefficient.Results: Out of 201 individuals, 46 (22.9%) and 155 (77.1%) students were male and female, respectively. The mean age of the students was 39.93±8.25 years. The mean values of the scores of self-directed learning outcomes and facilitators were 71.8±9.4 (out of 95) and 70.4±10.6 (out of 125), respectively. There was a direct and significant relationship between self-directed learning outcomes and facilitators (P<0.001); accordingly, with the increase of the score of facilitators, the score of self-directed learning also increased. Additionally, the variables of outcomes and facilitators had significant relationships with academic achievement (P<0.001).Conclusion: According to the study results, by increasing self-directed learning facilitators, the outcomes of this type of learning, especially students’ academic achievement, increased. Therefore, it is recommended to increase students’ participation and consolidate self-directed activities. Furthermore, by the application of technology and program appropriate to the subject of the course, professors in virtual training should strengthen and nurture students’ self-direction skills and guide them to do various assignments and activities related to their lesson objectives.